Microencapsulated Lemongrass (Cymbopogon flexuosus) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage. Issue 9 (21st October 2021) - Rampelotto, Cristine; Speroni, Caroline S.; Conte, Lisiane; Pianesso, Dirleise; Machado, Isadora S.; Rodrigues, Renata F.; Minuzzi, Natália M.; Adorian, Taida J.; Klein, Bruna; Wagner, Roger; Baldisserotto, Bernardo; da Silva, Leila P.; et al.
ABSTRACT: There is growing interest for using essential oils (EOs) in fish feed as they can improve fish health, growth, and productive yield. But, there is little information concerning their effects on fish flesh quality and whether EO residues can be found in flesh. The EO of lemongrass was recently demonstrated to increase the productive yield of silver catfish. Thus, the aim of this study was to evaluate the impact of lemongrass EO supplementation on physico-chemical properties, sensory acceptance, and stability during frozen storage of fish fillets. Silver catfish ( Rhamdia quelen ) were fed diets containing 0, 1, or 3 mL/kg of EO for 20 days. Fish were slaughtered, and fillets were stored at −20°C for 12 months and evaluated every 90 days. Dietary supplementation with EO did not affect proximate composition, fatty acid composition, or sensory acceptance of fish fillets. EO constituents (especially citral) were not detected in fish fillets. EO supplementation at 1 mL/kg appears to be more suitable to maintain physico-chemical changes similar to control during frozen storage. These data support the safety of lemongrass EO for use in aquaculture for human consumption purposes.